Deciphering the comprehensive microbiome of glacier-fed Ganges and functional aspects: implications for one health - Rachel Samson; Shubham Kumar; Syed Dastager; Krishna Khairnar; Mahesh Dharne (Microbiology Spectrum)
ABSTRACT Glacier-fed rivers are significant ecological components of the river catchments, yet their microbial diversity and the associated antimicrobial potential remain underexplored. The Ganges is a glacier-fed river of immense cultural, religious, and ecological significance that supports over 400 million people downstream, providing essential water for agriculture, industry, and daily use. Despite its importance, the microbial community composition and antimicrobial potential, across its relatively pristine origin, remain largely underexplored. One possible explanation for this could be the lower microbial load in the upstream glacier-fed region, which likely results in a reduced DNA yield, insufficient for whole-metagenome sequencing, in contrast to the more biologically diverse and nutrient-rich lower reaches. In this study, we developed an efficient DNA extraction and amplification method using low-input DNA to sequence the microbiome from sediments of the glacier-fed Ganges River in pre-monsoon and post-monsoon over 2 years. Taxonomic and functional diversity of bacterial and viral (phage) communities were analyzed, together with the seasonal variations in their composition. Significant differences in microbial communities were observed in response to seasonal shifts (P < 0.05). During the dry season, Proteobacteria and Actinobacteria were predominant, while Bacteroidetes and Firmicutes were abundant post-monsoon (P < 0.05). The microbiome harbors potential for the biosynthesis of streptomycin, phenylpropanoid, penicillin, and cephalosporins. Bacteriophages from Podoviridae, Myoviridae, and Siphoviridae showed lytic potential against putrefying and pathogenic bacteria. This first comprehensive study on the glacier-fed Ganges River highlights significant seasonal shifts in microbial diversity. The initial insights into the functional profile of the bacterial and phage diversity offer opportunities to explore various natural compounds and enzymes to tackle antimicrobial resistance under the one-health canopy.IMPORTANCEThis study addresses a knowledge gap by exploring the microbial diversity and antimicrobial potential of the glacier-fed Ganges River across different seasons. The findings reveal various taxa with biosynthetic capabilities for antimicrobial compounds. Additionally, the presence of bacteriophages with lytic potential opens up opportunities for their exploration and application spanning various domains of one health. These findings lay a foundational basis for understanding the unique properties of this riverine ecosystem and offer valuable insights into environmental conservation and the potential to tackle antimicrobial resistance.